THE EFFECT OF ORGANIZATIONAL COMMITMENT AND PROCEDURAL JUSTICE ON BUDGET PARTICIPATION AND VILLAGE PERFORMANCE IN MUARO JAMBI REGENCY - Rafiqoh R.; Mukhzarudfa; Yuliusman (Transpublika Publisher, 2023)
This study aimed to investigate the impact of organizational commitment and procedural justice on budget participation, as well as the influence of organizational commitment and procedural justice on village performance. Additionally, the study explored the relationship between budgetary participation and village performance in Muaro Jambi District. The target population for this research comprised village officials and members of the BPD (Badan Permusyawaratan Desa) in Muaro Jambi Regency, with a sample of 23 villages that received Village Fund Performance Allocations. Primary data was collected through questionnaires, and path analysis with Smart PLS was employed to analyze the data, examining both direct and indirect effects between the variables. The findings of the study revealed that organizational commitment and procedural justice had an impact on budget participation. Furthermore, organizational commitment and procedural justice were found to influence village performance, while budgetary participation also played a role in shaping village performance within Muaro Jambi District.